Synthesis and temperature-dependent studies of a perovskite-like manganese formate framework templated with protonated acetamidine. Issue 26 (19th June 2017) - Mączka, Mirosław; Janczak, Jan; Trzebiatowska, Monika; Sieradzki, Adam; Pawlus, Sebastian; Pikul, Adam
Abstract : Acetamidinium manganese formate undergoes a phase transition from the Imma to the P 21 / n structure at 304 K and magnetic order below 9 K. Abstract : We report the synthesis, crystal structure, thermal, dielectric, phonon and magnetic properties of the [CH3 C(NH2 )2 ][Mn(HCOO)3 ] (AceMn) compound. Our results show that this compound crystallizes in the perovskite-like orthorhombic structure, space group Imma . It undergoes a structural phase transition at 304 K into a monoclinic structure, space group P 21 / n . X-ray diffraction, dielectric, IR and Raman studies show that the ordering of the acetamidinium cations triggers the phase transition. Low-temperature magnetic studies show that this compound exhibits weak ferromagnetic properties below 9.0 K.